Is Heutagogy Inevitable? Insights Into Conceptions, Objectives, And Practices - Laala, Youcef (جامعة الوادي - University of Eloued, 2021)
Heutagogy is by definition the study of self-determined learning, based on the theory, which says that the focus in learning should be on what, and how learners want to learn rather than what is to be taught. Self-determined learning urges the shift from a teacher-centred learning to a learner-centred one in which the learners can invest in their autonomy, selfefficacy and different metacognition skills. The aim of Heutagogy is to create life-long learners equipped with adequate tools, including technology to face the complexities of the work place, which requires universal potentials capable of solving different problems in different contexts. The renewal of this approach is not accidental but a result of an extension of Andragogy and the emergence of advanced technology helping distance education and the need to generalize practices based on distance instruction and guidance among teachers, instructors and lecturers using new technology like social media to deliver pedagogical content. Based on a review of current research and literature, this paper discusses the concept of Heutagogy and Andragogy, and the importance of distance learning within the integration of technology.
مقال
Keywords: Heutagogy, self-determined learning, self- directed learning, Andragogy, distance learning, the SIDE Model